2005
DOI: 10.1016/j.jtcvs.2004.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing revascularization strategies in patients with multivessel coronary disease: Impact of intracoronary pressure measurements

Abstract: In patients with multivessel disease, coronary pressure-derived fractional flow reserve is a valuable tool to guide clinical decision making and support cardiologists and cardiovascular surgeons in the composition of optimal revascularization strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Much debate currently exists as to when practitioners should transfuse patients with coronary artery disease (CAD) (17). This consideration is likely to be of less applicability to straightforward elective cardiac surgery where patients have undergone myocardial revascularization, at least in part restoring coronary reserve or had significant CAD excluded preoperatively (18). In addition, animal studies have demonstrated that a viscosity mediated increase in transstenotic flow rate may act to maintain myocardial oxygenation (19).…”
Section: Discussionmentioning
confidence: 99%
“…Much debate currently exists as to when practitioners should transfuse patients with coronary artery disease (CAD) (17). This consideration is likely to be of less applicability to straightforward elective cardiac surgery where patients have undergone myocardial revascularization, at least in part restoring coronary reserve or had significant CAD excluded preoperatively (18). In addition, animal studies have demonstrated that a viscosity mediated increase in transstenotic flow rate may act to maintain myocardial oxygenation (19).…”
Section: Discussionmentioning
confidence: 99%
“…Since LMCA disease is frequently associated with CAD elsewhere in the coronary tree, these properties are particularly valuable because uncertainty about the contribution of the LMCA to the clinical syndrome may confuse the issue of whether to pursue medical or revascularization therapy. Several studies have shown that in many cases of multivessel CAD (with or without left main involvement), discrepancies between the angiographic and functional disease status exist [41,50,51].…”
Section: Considerations On and Limitations Of Ffr Measurements In Lmcmentioning
confidence: 99%
“…12 An important consideration in cardiac surgical patients is that these individuals, in the majority of cases, have either undergone coronary revascularisation which has normalised coronary reserve or had angio-graphically significant CAD excluded preoperatively. 13 Our rigid transfusion threshold of 8 g/dl postoperatively, and exclusion from the study of all patients who received a transfusion after the first 24 h, created a uniform "playing field" for all patients in the study. This allowed us to compare their TBW, bodyweight and [Hb] in a meaningful way after the first post-operative day.…”
Section: Reduction In Body Weight Was Associated With An Increase In mentioning
confidence: 99%